2022
DOI: 10.3389/fphys.2022.816218
|View full text |Cite
|
Sign up to set email alerts
|

C1q/Tumor Necrosis Factor-Related Protein 9: Basics and Therapeutic Potentials

Abstract: C1q/tumor necrosis factor-related protein 9 (CTRP9) is a newly discovered adipokine that is the closest paralog of adiponectin. Proteolytic cleavage of CTRP9 leads to the release of the globular domain (gCTRP9), which serves as the major circulating subtype. After binding with adiponectin receptor 1 (AdipoR1) and N-cadherin, CTRP9 activates various signaling pathways to regulate glucose and lipid metabolism, vasodilation and cell differentiation. Throughout human development and adult life, CTRP9 controls many… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 116 publications
0
4
0
Order By: Relevance
“…As mentioned earlier, CTRP9 has the potential to be an option for improving glucose‐related metabolic syndrome 78 . Previous data showed that serum levels of leptin and adiponectin were significantly lower in patients with type 2 diabetes, 79 which would be predictive of circulating CTRP9 54,79,80 .…”
Section: The Prognostic Potential Of Ctrp9 Regarding Metabolic Disord...mentioning
confidence: 86%
See 1 more Smart Citation
“…As mentioned earlier, CTRP9 has the potential to be an option for improving glucose‐related metabolic syndrome 78 . Previous data showed that serum levels of leptin and adiponectin were significantly lower in patients with type 2 diabetes, 79 which would be predictive of circulating CTRP9 54,79,80 .…”
Section: The Prognostic Potential Of Ctrp9 Regarding Metabolic Disord...mentioning
confidence: 86%
“…As mentioned earlier, CTRP9 has the potential to be an option for improving glucose‐related metabolic syndrome. 78 Previous data showed that serum levels of leptin and adiponectin were significantly lower in patients with type 2 diabetes, 79 which would be predictive of circulating CTRP9. 54 , 79 , 80 It has also been indicated that serum levels of CTRP9 were remarkably correlated with systolic pressure and C‐reactive protein levels in diabetic subjects.…”
Section: The Prognostic Potential Of Ctrp9 Regarding Metabolic Disord...mentioning
confidence: 96%
“…CTRP9 was reported to regulate the pathological processes associated with obesity [21], lipid metabolism [22], cardiovascular disease [23], myocardial ischemia [24], apoptosis [25], and pulmonary artery pressure [26]. Thus, these critical roles of CTRP9 in pathological and physiological conditions have piqued the interest of the scientific community [27]. However, the effect of CTRP9 on brown adipocyte formation and lipid metabolism has not been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…C1q/tumor necrosis factor-related protein 9 (CTRP9) is a recently discovered adipokine within the CTRP superfamily, playing a pivotal role in regulating glycolipid metabolism and providing cardioprotection ( Zhao et al, 2018 ; Guan et al, 2022 ). Clinical investigations have unveiled a correlation between lower CTRP9 levels and metabolic syndrome, and insulin resistance in diabetic individuals ( Hwang et al, 2014 ; Jia et al, 2017 ; Moradi et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%